2013
DOI: 10.1589/jpts.25.1397
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Vertical Load on Gluteus Medius Activity and Gait Characteristics during Walking

Abstract: [Purpose] The present study examined the activity and the gait characteristics of the gluteus medius and the trunk stability muscles during the stance phase of gait on level ground when a vertical load corresponding to 0%, 1%, or 2% of body weight was placed on the lower extremities during the swing phase of the gait. [Methods] The subjects were 40 young males aged between 21 and 30 years. The vertical load, corresponding to 0%, 1%, 2% of weight, which was measured with an electronic scale, was placed bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Based on our findings, it appears that, compared with healthy individuals, those with ACLD experience substantial reductions in peak knee-flexion angle, peak knee-adduction angle, peak external knee-flexion moment, and peak external knee-adduction moment. These adaptations have been linked to muscle weakness, 33 specifically of the quadriceps in the sagittal plane and the lateral hip musculature in the frontal plane, 49,50 which is consistent with common clinical findings after ACL injury. 51,52 Interestingly, in most studies included in this review, these adaptations persisted through the first year after ACLR despite the surgical restoration of knee-joint stability.…”
Section: Discussionsupporting
confidence: 78%
“…Based on our findings, it appears that, compared with healthy individuals, those with ACLD experience substantial reductions in peak knee-flexion angle, peak knee-adduction angle, peak external knee-flexion moment, and peak external knee-adduction moment. These adaptations have been linked to muscle weakness, 33 specifically of the quadriceps in the sagittal plane and the lateral hip musculature in the frontal plane, 49,50 which is consistent with common clinical findings after ACL injury. 51,52 Interestingly, in most studies included in this review, these adaptations persisted through the first year after ACLR despite the surgical restoration of knee-joint stability.…”
Section: Discussionsupporting
confidence: 78%
“…A study that examined the activation of the lower limb in the stance phase during walking using diverse weight amounts (0 kg, 0.5 kg, and 1 kg) reported a significant difference in the case of 0.5 kg vertical loading ( Lee et al, 2013 ). Lee (2013) studied weight loading that corresponded to 0%, 1%, and 2% of body weight on the lower limbs in the swing phase side of 40 young men in their 20s and 30s and compared the activity of the gluteus medius muscle in the stance phase side. The study reported a significant activation of the gluteus medius muscle in the case of 1% loading.…”
Section: Resultsmentioning
confidence: 99%
“…A study reported that exercise effects increase when the attachment location of the weight load is nearer to the lower limb than the upper limb and that the minimum weight loading is 2% of body weight, with 1% on each lower limb ( Yang, 1996 ). A study that compared the activity of the gluteus medius muscle during walking by applying a weight load of 0%, 1%, and 2% of body weight reported significant activation in the case of 1% loading ( Lee, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…They found that muscle activity increased when 0.5 kg of vertical load was applied to the lower extremities in the swing phase compared to normal gait, whereas counterintuitively the muscle activity decreased when 1 kg of vertical load was applied, comparied to the 0.5 kg load. In addition, they noted that among loads of 0, 1 and 2% of body weight, the most appropriate weight for strengthening the gluteus medius was a vertical load of 1% of body weight 8 ) . Furthermore, Jung et al 9 ) measured the muscle activity in the gluteus medius during walking on a treadmill set at angles of 0°, 5°, and 10°, and they showed that the muscle activity was the highest at when the treadmill angle was 5°.…”
Section: Introductionmentioning
confidence: 99%